Program Dukungan Kesehatan Mental Emosional Melalui Psikoterapi Pada Pasien Gagal Ginjal Kronik - Mardiati Agustin, Ike; Sumarsih, Tri; Ernawati, Ernawati (Yayasan Inspirasi El Burhani, 2024)
Introduction Introduction Chronic kidney failure (CKD) patients not only experience physical problems but also psychosocial and spiritual problems. One of the psychosocial problems that can be experienced is anxiety and depression, a form of therapy program is needed to reduce the level of anxiety and depression in CKD patients, one of the therapies that can be given is a non-pharmacological therapeutic approach through psychotherapy, namely Spiritual Emotional Freedom Technique (SEFT) and affirmations. Purpose of this activity to help overcome the problems of chronic diseases and comorbid chronic kidney disease with anxiety and depression through the SEFT psychotherapy program to reduce the level of depression in kidney disease patients with hemodialysis therapy. This activity was given to 25 CKD patients who were treated in the Hemodialysis Room at PKU Muhammadiyah Gombong Hospital. Through the provision of psychotherapy given over 3 meetings, with a duration of therapy of 30 minutes for SEFT and 15 minutes for positive affirmations. Level of anxiety and depression before and after being given the activity is measured using HADS. The results of the activity showed that there was a decrease in the level of anxiety and depressions of GGK Client before being given therapy.Conclusion This program is recommended as an effort to overcome anxiety and depression in patient with kidney chronic disease